Perbedaan Reaksi Pasar Modal Sebelum dan Sesudah Pengumuman Presiden Terpilih Tahun 2019 (Studi pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia) - Asyara Okta Aulia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
This research aims to determine difference between stock price, abnormal return, trading volume activity and bid-ask spread before and after the announcement of president elected in 2019. Type of research uses event study method with total samples of 45 companies based on purposive sampling technique. The research used test Multiple Discriminant Analysis with SPSS 26 program analysis tool. Result of research show that partially there is a significant difference of abnormal return and bid-ask spread before and after event with a significant value is 0.000 and there is no significant difference of stock price and trading volume activity before and after event with a significant value is 0.938 and 0.919. Furthermore, the result of Wilk’s Lambda test show that simultaneously there are significant differences between stock price, abnormal return, trading volume activity and bid-ask spread before and after the announcement of president elected in 2019 with a significant value is 0.000.